Teacher Strategies in Improving the Quality of Students at MTs 2 Medan Country - Muhayya Meutia (International Journal Of Education, Social Studies, And Management (IJESSM), 2021)
Every teacher who teaches at MTs Country 2 Medan is required to complete a very adequate learning administration, facilities, and infrastructure. The principal of the madrasa also provides excellent care for subordinates by arriving on time. Based on these problems, the researcher wanted to research strategies in improving the quality of education at Mts Country 2 Medan. As that becomes a problem in the research of this is the S Strategy of teachers in improving the quality of Learners, Implementation Strategies teachers to improve the quality of Participants Didik, Constraints any experienced by teachers in improving the quality of students. The method of research that is used is a qualitative descriptive approach. The research results. S Strategy of teachers in improving the quality of students, by meeting MGMPs (Council Subject Teacher) regularly and scheduled, all subject teachers must complete ad m in stars learning such as syllabus, Education Calendar, Annual Program, Program Semester, Rpp and others. The implementation of strategies in improving the quality of students at MTs Country 2 Medan is carried out with many programs, including morning apples every Tuesday and Wednesday of speech material from students, then every day there is gerbaning (silent reading movement), everyone in MTs N 2 field reading books, later reviewed then students convey to the teacher in front. Every Friday there is a yasin reading activity called Friday preaching, the activity aims to improve students' talents. As for the obstacles faced by the head of the madrasah in improving the quality of educators, some teachers do not keep up with the changes and one of the obstacles experienced by MTs Country 2 Medan teachers in training programs and one-way schedule coincides with the teaching schedule.